MTs Principal Strategies in Strengthening Character Education in Kendal District - Firdaus Himawan Raharjo; Wiwik Wijayanti (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
The decline in student character is reflected in weakened discipline, reduced respect for educators, and low social awareness. This study aims to reveal the leadership strategies of madrasah principals in strengthening character education at MTs Negeri 2 Kendal and MTs NU 07 Patebon, Kendal Regency. Using a qualitative approach with a descriptive design, data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, presentation, and conclusion drawing. The findings indicate that principal leadership plays a vital role in shaping student character through role modeling, habituation, integrated learning, and creating a religious and inclusive school climate. Supporting factors include a conducive school environment, collaboration with parents, and teachers as role models. Challenges include weak family supervision, negative impacts of technology, and low student commitment. The success of these strategies is reflected in students’ affective scores and the development of responsible, high-quality individuals who contribute positively to society